Study of prognostic factors in multiple myeloma - Rathnakumar, Geeta; Ghosh, Kinjalka; Choudhary, Nikhil; Kamble, Narendra; Inamdar, Nitin (International Journal of Advances in Medicine, 2021)
Background: Multiple myeloma (MM) is cancer of the plasma cell characterized by interpatient heterogeneity, in most of the cases it is incurable. It is the second most common hematological malignancy. Overall survival of patients has significantly increased recently. Lot of research is going on for prognostic factors, which can predict disease and response to therapy. During the past decades, biomarkers: M protein and β2 microglobulin have shaped the knowledge about MM. This study was undertaken to evaluate the role of prognostic factors in newly diagnosed and few follow up patients of MM before, during and after the treatment in Indian population. Methods: We analyzed 177 samples (90 MM patients and 87 healthy control) for creatinine, calcium, phosphorus, LDH, total protein, albumin, globulin, β2M, Immunoglobulines (Igs), IgG, IgA, IgM, Kappa light chain and Lambda light chains, serum protein electrophoresis (SPE) and immunofixation electrophoresis (IFE). Results: The result of our study are significant at p<0.0001 for creatinine, β2M, LDH, albumin, globulin and immunoglobulins whereas for calcium and phosphorus results are not significant at p<0.005. We observed that the levels of β2m, creatinine, LDH and M band concentration declined during the treatment (chemotherapy). Conclusions: We conclude that these results will help the clinicians to tailor-made the chemotherapy doses for betterment of patients and improve survival rate in MM patients.